Optimalisasi Manajemen Properti pada Medium Tank Harimau Melalui Peningkatan Tingkat Kandungan dalam Negeri - Achmad Imron; Rudi Haposan Siahaan; Handy Oktavianus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Tanks are properties that have high economic value and are strategic to maintain the sovereignty of the Republic of Indonesia, but until now they have faced obstacles with low TKDN (Domestic Content Level) so that Indonesia has a high dependence on other countries for defense and security equipment. This study aims to increase the TKDN value of the Tiger Medium Tank and is part of Property Management to be more optimal economically and defense-wise. The research is a qualitative study, in the form of a case study of the Medium Tank produced by PT Pindad. The data were collected using the inspection method, micro identification, and interviews with 21 expert sources who were considered to be able to represent stakeholders, namely PT. Pindad as a producer, several supporting industries, users and regulators in this case the Ministry of Industry and the Ministry of Defense and KKIP (Defense Industry Policy Committee). The data was processed using NVivo software to structure the findings. Three points from this study are to increase TKDN. First, review the rules for calculating TKDN specifically for defense and security equipment. The method for calculating TKDN which is currently only cost-based must be combined with process-based, and followed by special implementation rules for defense and security equipment products. Second, efforts that must be made, which include: government policies, commitments, building an ecosystem, and component & subcomponent substitution. Third, this study identifies import substitution component and subcomponent industries that can be developed either through intensification of existing industries or extensification by creating new industries to encourage the formation of an industrial ecosystem that increases TKDN.